Biphasic calcium phosphate scaffolds fabricated by direct write assembly: Mechanical, anti-microbial and osteoblastic properties. Issue 1 (January 2017) - Marques, Catarina F.; Perera, Fidel Hugo; Marote, Ana; Ferreira, Sónia; Vieira, Sandra I.; Olhero, Susana; Miranda, Pedro; Ferreira, José M.F.
Abstract: The present work reports on the fabrication of 3-D porous calcium phosphate scaffolds by robocasting from biphasic (HA/β-TCP ≈ 1.5) powders, undoped and co-doped with Sr and Ag. Scaffolds with different pore sizes and rod diameter of 410 μm were fabricated and sintered at 1100 °C. The size and morphology of the powder particles, and the concentrations of the processing additives, were shown to play major roles in the robocasting process. For all pore sizes tested, the compressive strength of scaffolds was comparable to or even higher than that of cancellous bone, and mechanical data could be systematically correlated with the porosity fraction. Co-doping the starting powders with Sr and Ag enhanced the mechanical strength of scaffolds, conferred good antimicrobial activity against Staphylococcus aureus and Escherichia coli, and did not induce any cytotoxic effects on human MG-63 cells. Furthermore, the co-doped powder was more effective in inducing pre-osteoblastic proliferation.